Developing a Health Equity and Criminal Justice Concentration for a Master of Public Health (MPH) Program: Results From a Needs Assessment Among Community Partners and Potential Employers - Hernandez, Alexandra L.; Green, Mathew; Kelly, Nemesia; Strouse, Carly; Mackie, Trina; Cummings, Gayle; Lingas, Elena O. (Frontiers in Public Health, 2019)
The United States has experienced a 4-fold increase in jail and prison populations over the last 40 years, disproportionately burdening African American and Hispanic/Latinx communities. Mass incarceration threatens the health of individuals, families, and communities, and requires a public health response. The Master of Public Health (MPH) Program at Touro University California (TUC) trains students to become skillful, socially-conscious public health professionals. We are developing a concentration focused on the public health impacts of incarceration. Along with the core public health curriculum, students of this new “Health Equity and Criminal Justice (HECJ)” concentration will receive training in criminal justice, reentry, reintegration, recidivism, restorative justice, structural racism, and social and community impacts of incarceration. Our study gauges interest in an HECJ concentration in our local community, including potential employers. We surveyed a cross-section of community partners including public health departments, other governmental agencies, California correctional facilities, county jails, community groups, health clinics, and hospitals. A majority (89%) of respondents consider mass incarceration a public health problem and 86% believe specialized training would make graduates employable by criminal justice related organizations. The HECJ track will fill a gap in the field and train a future generation of public health professionals to address the epidemic of mass incarceration.